Relationship Between Depression, Anxiety Levels, and Coping Mechanisms in Patients with Congestive Heart Failure - Afrida, Yuni; Fitri, Nurwijaya; Mardiana, Nova (Genius Journal, 2025)
Introduction: Congestive heart failure is a serious medical condition that often experiences severe physical symptoms and significant psychological distress, including depression and anxiety. Coping mechanisms are strategies used by patients with congestive heart failure to deal with depression and anxiety related to their medical condition. Patients with adaptive coping mechanisms can better manage symptoms and reduce the risk of depression and anxiety. However, patients with maladaptive coping mechanisms are more vulnerable to psychological distress. Objective: This study aimed to determine the relationship between depression and anxiety levels and coping mechanisms in congestive heart failure patients attending the Heart Polyclinic of Sejiran Setason Regional General Hospital in 2025. Method: This study used a cross-sectional design and chi-square test, with univariate and bivariate analyses. The study was conducted from May 21 to June 10, 2025. The population was 138 outpatients with congestive heart failure who were admitted to the Heart Polyclinic of Sejiran Setason Regional General Hospital between January and February. The sample consisted of 67 congestive heart failure patients. Result: The results of this study indicate a relationship between depression (ρ = 0.016) and anxiety (ρ = 0.000) and coping mechanisms in patients with congestive heart failure. Conclusion: This study suggests that it can serve as a basis for developing a holistic care program for patients with congestive heart failure, one that focuses not only on managing physical symptoms but also on psychological aspects and enhancing patients' coping skills to face daily challenges.